(untitled) (Annals of Medical Research, 2021)
Aim: Candidemia are one of the most important causes of mortality and morbidity in inpatients, and their importance is increasing with the increasing number of immunosuppressive patients and the widespread use of invasive procedures and broad spectrum antibiotics in recent years. In our study, we aimed to identify Candida species isolated from blood cultures and to determine the antifungal susceptibility rates of adult patients who were hospitalized in Malatya Education and Research Hospital Intensive Care Units between July 2015 and July 2019, and had Candida growth in at least one of their blood cultures.Materials and Methods: The blood cultures isolated from adult intensive care units patients and sent to the Microbiology Laboratory of our hospital over the four years, were examined retrospectively. Species distribution and antifungal susceptibility were determined using VITEK 2 Compact System (BioMerieux, France).Results: Of the 123 clinical samples, 59 (48%) were C. albicans, 21 (17.1%) were C. parapsilosis, 18 (14.6%) were C. tropicalis, 12 (9.8%) were C. glabrata, 5 (4.1%) were C. kefyr, 2 (1.6%) were C. krusei, 2 (1.6%) were C. lipoliytica, 2 (1.6%) were C. lusitaniae, 1 (0.8%) was C. dubliniensis and 1 (0.8%) was C. pelliculosa. 96.5% of C. glabrata strains were found to be susceptible to amphotericin-B, 93.1% to fluconazole, 98.3% to voriconazole, 93.5% to caspofungin, 91.4% to micafungin and 96.7% to flucytosine. 98.1% of nonalbicans Candida (NAC) strains were found to be susceptible to amphotericin-B, 74.6% to fluconazole, 90.7% to voriconazole, 78.4% to caspofungin, 80% to micafungin and 100% to flucytosine.Conclusion: The highest resistance to antifungals was found in C. glabrata and the highest susceptibility was observed in C. tropicalis. In order to develop effective and accurate infection control strategies and reduce mortality and morbidity, it is important to know the distribution and susceptibility of infectious agents, especially in critical patients in intensive care units.